2005
DOI: 10.1111/j.1526-4610.2005.05136.x
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Brainstem Lesions With Migraine‐Like Headache: An Imaging Study of Multiple Sclerosis

Abstract: The results of this study indicate that the presence of a midbrain plaque in patients with MS is associated with an increased likelihood of headache with migraine characteristics. (Headache 2005;45:670-677).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
98
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(113 citation statements)
references
References 32 publications
8
98
1
1
Order By: Relevance
“…Migraine was more frequent in RR and tension type was more frequent in SP, more commonly seen in female patients (26). When MS patients without headaches, MS patients with migraines and non-MS patients with migraines were compared in terms of their MRI findings, MS patients with migraine were seen so have high lesion load in the periaqueductal area (an important region for antinociceptive control) (27). There was headache in 47% of our cases and 2 of them were migraine, 2 were induced by interferon, and the rest were tension type.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine was more frequent in RR and tension type was more frequent in SP, more commonly seen in female patients (26). When MS patients without headaches, MS patients with migraines and non-MS patients with migraines were compared in terms of their MRI findings, MS patients with migraine were seen so have high lesion load in the periaqueductal area (an important region for antinociceptive control) (27). There was headache in 47% of our cases and 2 of them were migraine, 2 were induced by interferon, and the rest were tension type.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that migraine prevalence is high in MS patients with brainstem demyelinating plaques in the red nucleus [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…A hypothesis has been proposed, relating MS relapse-onset migraine headache to a possible dysregulation of the 5-HT system in the pathophysiology of MS (Sandyk and Awerbuch, 1994). In a comparative study including migraineurs and MS patients with and without migraine, Tortorella et al (2006) found that MS patients with migraine had more lesions in the red nucleus, substantia nigra and periaqueductal gray matter, thus suggesting a possible localization factor responsible for the presence of migraine in patients with MS. Brainstem and especially midbrain plaques in patients with MS could be associated with an increased likelihood of migraine headache as well (Gee et al, 2005). But while MS patients tend to have migraine or other types of headache as comorbidities, no distinctive "MS headache" can be described, and headache may not correlate with any clinical features of MS (Rolak and Brown, 1990).…”
Section: Introductionmentioning
confidence: 99%